2013
DOI: 10.1186/1471-2458-13-845
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported exposure to intimate partner violence among women and men in Sweden: results from a population-based survey

Abstract: BackgroundFew population-based studies assessing IPV among randomly selected women and men have been conducted in Sweden. Hence, the aim of the current study was to explore self-reported exposure, associated factors, social and behavioural consequences of and reasons given for using psychological, physical and sexual intimate partner violence (IPV) among women and men residing in Sweden.MethodsCross-sectional postal survey of women and men aged 18–65 years. Bivariate and multivariate logistic regression analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
71
2
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(93 citation statements)
references
References 45 publications
(70 reference statements)
12
71
2
5
Order By: Relevance
“…Recent studies have reported that sex-differences might be only found in lifetime victimization and perpetration estimates when compared to past year estimates, reflecting women's more severe experiences (Lovestad and Krantz 2012;Nybergh et al 2013). However, an analysis of lifetime prevalence for the four types of IPV assessed (Supplementary Tables 5, 6) revealed the same crosscountry differences as noted for past year estimates and sex-differences within each site also followed the same pattern found for past year estimates.…”
Section: Differences Between Sexesmentioning
confidence: 57%
See 2 more Smart Citations
“…Recent studies have reported that sex-differences might be only found in lifetime victimization and perpetration estimates when compared to past year estimates, reflecting women's more severe experiences (Lovestad and Krantz 2012;Nybergh et al 2013). However, an analysis of lifetime prevalence for the four types of IPV assessed (Supplementary Tables 5, 6) revealed the same crosscountry differences as noted for past year estimates and sex-differences within each site also followed the same pattern found for past year estimates.…”
Section: Differences Between Sexesmentioning
confidence: 57%
“…Nevertheless, the British Crime Survey (Khalifeh et al 2013) points to past year estimates of physical IPV against men of 1.3 % and of 2.0 % against women, whereas in Denmark (Sorensen et al 2012) these were 6.4 % in men and 5.0 % in women, lower than our results. Two studies conducted in Sweden (through post), one using the WHO tool (Nybergh et al 2013) and another using the CTS2 (Lovestad and Krantz 2012) showed that past year physical IPV against men was 7.6 and 11 %, respectively, and against women it was 8.1 and 8 %, while sexual IPV male victims were 2.3 and 0.6 % and female victims were 3.0 and 3.2 %. Also a study conducted among women living in Germany (Stockl et al 2011) showed that 15 % ever experienced physical violence and 17 % experienced physical or sexual violence.…”
Section: Intimate Partner Violence Prevalencementioning
confidence: 99%
See 1 more Smart Citation
“…Also, ignoring gender when considering violence ignores the impact violence have on also those not directly exposed, such as fear of rape among many women (Muehlenhard and Kimes, 1999 (Nybergh et al, 2013a) and 27% (Lovestad and Krantz, 2012). Among men, the figures have been reported to be 8% (National Board of Health and Welfare, 2014b), 14% (Nybergh et al, 2013a) and 21% (Lovestad and Krantz, 2012). In this thesis I report figures of 10% for women and 3% for men.…”
Section: Gender and Interpersonal Violencementioning
confidence: 85%
“…On a societal level, power imbalances with gender norms supporting male dominance in families and in some cases even men's use of violence against their female intimate partners, facilitate intimate partner violence against women (Baker et al, 2013). Also, ignoring gender when considering violence ignores the impact violence have on also those not directly exposed, such as fear of rape among many women (Muehlenhard and Kimes, 1999 (Nybergh et al, 2013a) and 27% (Lovestad and Krantz, 2012). Among men, the figures have been reported to be 8% (National Board of Health and Welfare, 2014b), 14% (Nybergh et al, 2013a) and 21% (Lovestad and Krantz, 2012).…”
Section: Gender and Interpersonal Violencementioning
confidence: 99%